2009
DOI: 10.1111/j.1365-294x.2009.04408.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid adaptive divergence between ecotypes of an aquatic isopod inferred from FSTQST analysis

Abstract: Divergent natural selection is often thought to be the principal factor driving phenotypic differentiation between populations. We studied two ecotypes of the aquatic isopod Asellus aquaticus which have diverged in parallel in several Swedish lakes. In these lakes, isopods from reed belts along the shores colonized new stonewort stands in the centre of the lakes and rapid phenotypic changes in size and pigmentation followed after colonization. We investigated if selection was likely to be responsible for these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
51
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(60 citation statements)
references
References 55 publications
9
51
0
Order By: Relevance
“…Recently, it has been argued that comparisons of population divergence between putatively adaptive traits (often referred to as "Q ST ") and neutral population divergence (F ST ), should utilize the whole neutral F ST -distribution to see if the adaptive traits fall within this distribution, before the null hypothesis of genetic drift can be safely rejected [16,44]. We follow these recommendations and visualized the entire neutral F ST -distribution and its relationship to our adaptive trait (color morph divergence).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been argued that comparisons of population divergence between putatively adaptive traits (often referred to as "Q ST ") and neutral population divergence (F ST ), should utilize the whole neutral F ST -distribution to see if the adaptive traits fall within this distribution, before the null hypothesis of genetic drift can be safely rejected [16,44]. We follow these recommendations and visualized the entire neutral F ST -distribution and its relationship to our adaptive trait (color morph divergence).…”
Section: Methodsmentioning
confidence: 99%
“…One possible approach might be to study whether the population distribution of a heritable phenotypic character differs from the neutral expectation or not [7,15,16] . Neutral genetic markers can be used to estimate the effective population sizes (N e ), and from such data, the expected probability of fixation of neutral and selected alleles can be calculated.…”
Section: Introductionmentioning
confidence: 99%
“…We do not have estimates of heritabilities or among-population genetic variances, which are usually a prerequisite for this type of indirect inference, namely F ST -Q ST comparisons (Merilä and Crnokrak, 2001;Eroukhmanoff et al, 2009;reviewed by Whitlock 2008). However, it is possible, with appropriate caution, to instead use phenotypic variance components corrected for the missing quantitative genetic estimates in such analyses (see for example, Saether et al, 2007).…”
Section: Phenotypic Traits Under Selection and The Role Of Environmenmentioning
confidence: 99%
“…Indirect inferences of selection, based on comparisons of F st /Q st divergence [cf. 36], on these four ecotype populations have furthermore shown that differentiation between the ecotype populations is far greater than if driven by neutral processes like genetic drift alone [37] The main cause for ecotype divergence is suggested to be habitat-differences in predation regimes, either the number or types of predators, or a combination [31].…”
Section: Introductionmentioning
confidence: 99%